Prospective evaluation of early treatment outcome in patients with meningiomas treated with particle therapy based on target volume definition with MRI and 68Ga-DOTATOC-PET - Combs, Stephanie; Welzel, Thomas; Habermehl, Daniel; Rieken, Stefan; Dittmar, Jan Oliver; Eitz, Kerstin Anne; Jäkel, Oliver; Haberkorn, Uwe; Debus, Jürgen (Acta oncologica, 2013)
Purpose. To evaluate early treatment results and toxicity in patients with meningiomas treated with particle therapy. Material and methods. Seventy patients with meningiomas were treated with protons (n = 38) or carbon ion radiotherapy (n = 26). Median age was 49 years. Median age at treatment was 55 years, 24 were male (34%), and 46 were female (66%). Histology was benign meningioma in 26 patients (37%), atypical in 23 patients (33%) and anaplastic in four patients (6%). In 17 patients (24%) with skull base meningiomas diagnosis was based on the typical appearance of a meningioma. For benign meningiomas, total doses of 52.2-57.6 GyE were applied with protons. For high-grade lesions, the boost volume was 18 GyE carbon ions, with a median dose of 50 GyE applied as highly conformal radiation therapy. Nineteen patients were treated as re-irradiation. Treatment planning with MRI and 68-Ga-DOTATOC-PET was evaluated. Results. Very low rates of side effects developed, including headaches, nausea and dizziness. No severe treatment-related toxicity was observed. Local control for benign meningiomas was 100%. Five of 27 patients (19%) developed tumor recurrence during follow-up. Of these, four patients had been treated as re-irradiation for recurrent high-risk meningiomas. Actuarial local control after re-irradiation of high-risk meningiomas was therefore 67% at six and 12 months. In patients treated with primary radiotherapy, only one of 13 patients (8%) developed tumor recurrence 17 months after radiation therapy (photon and carbon ion boost). Conclusion. Continuous prospective follow-up and development of novel study concepts are required to fully exploit the long-term clinical data after particle therapy for meningiomas. To date, it may be concluded that when proton therapy is available, meningioma patients can be offered a treatment at least comparable to high-end photon therapy.
Im Titel ist "68" hochgestellt
Gesehen am 07.05.2021